Impact of Removing Race Adjustment When Estimating GFR on Chronic Kidney Disease Staging. (28th October 2021) - Cai, C; Sahor, F; Wilson, B; Veeramachaneni, T; Hashim, I
Abstract: Introduction/Objective: Determination of glomerular filtration rate (GFR) is essential in assessment of kidney function, particularly in patients with chronic kidney disease (CKD). Formulas were developed to calculate estimated GFR (eGFR), as direct measurement is cumbersome and not amenable to routine monitoring. CKD-EPI is the most widely used formula for eGFR, using parameters of serum creatinine, gender, race, and age. A race adjustment was added from an unfounded assumption that Black patients have more muscle mass, increasing their eGFR by about 16%. There is concern on the impact of "correcting" for Black race on patient management, utility of eGFR, and its possible contribution to healthcare disparities. This study examined the impact of eliminating race adjustment from the CKD- EPI formula on CKD staging in patients at a large safety-net hospital in an academic medical center. Methods/Case Report: 80090 serum creatinine values from 56676 adult patients (31.4% Black, 67.5% female, median age 51 yrs) were collected from the electronic medical record (Epic, Verona, WI) over a 16-month timeframe. Values were excluded if they lacked age, gender, self-identified race, or serum creatinine. eGFR was calculated using the CKD-EPI equation with and without race modifier, and CKD staging was performed using 2012 Kidney Disease: Improving Global Outcomes guidelines. Results (if a Case Study enter NA): In our cohort, only 50.8% of Black patients are in CKD1, indicative of no CKD, compared to 67.9% of non-Black patients. Given that these two cohorts are demographically similar, this shows a discrepancy in kidney function even before removing the race adjustment. After removal of the race modifier, 28.1% of Black patients were reclassified into a more severe CKD stage. The most restaging occurred from CKD3A to 3B (39%). Conclusion: Many Black patients in our study were reclassified to a more severe CKD stage, with the highest percentage of patients restaged to CKD3B, which would have attracted clinical attention for nephrology referral. We recommend removal of the race adjustment in eGFR, given its basis in the incorrect belief in biological differences between races. It perpetuates systemic racism and discrimination in healthcare, and its removal will provide more equitable care and reduce healthcare disparities. Future studies should examine the increase in resources required to provide adequate medical care to patients who will be placed into a more severe CKD stage.